Artificial intelligence to predict loyalty to university - Cachón Rodríguez, Gabriel; Gomez Martinez, Raul; Martinez-Navalon, Juan-Gabriel; Prado-Roman, Camilo (Journal of Management and Business Education, 2019)
Due to the loss of competitiveness of public institutions of higher education this research analyzes the visual identity, communication, behavior, corporate culture and image as predictors of loyalty in a public institution of higher education. For the analysis of the data, the Bayesian network's method is used. The results show that artificial intelligence has a predictive capacity of loyalty. Finally, research indicates a series of implications for the survival of these institutions.